Group therapy for adults with severe mental illness : adapting the tavistock method - Semmelhack, Diana. (Advances in mental health research series., 2013)
"Mental illness is prevalent in society with a quarter of individuals having a diagnosable mental illness. A growing percentage of these individuals develop severe disorders which incapacitate them and may leave them unemployed, lonely, isolated and untreated. In recent years, there has been a movement away from therapy, and a heightened emphasis on medicalization. This book argues that medication alone does not take away the deep emotional pain of feeling isolated and lonely, and considers the modification of the client's social relationships as a critical ingredient in any treatment. Group Therapy for Adults with Severe Mental Illness explores a non-traditional application of treatment known as the group-as-a-whole model. This approach to group work derives from the Tavistock tradition, in which emphasis on the whole group versus any specific member makes the group a safe place to risk sharing and confronting painful issues. This text highlights the efficacy of utilizing this model in the treatment of severely mentally ill consumers in various settings including jails, nursing homes and group homes. Included in the book: -case studies using the Tavistock method -the power of group-as-a-whole work in educating mental health professionals and graduate students -the use of the model to enhance creative expression in the arts -the use of the model to understand larger social systems This text will be of value to mental health professionals, researchers and educators interested in the treatment of severely mentally ill populations in institutional settings, and individuals with a specific interest in group psychotherapy"--